I escaped pirates in the Caribbean - Crowe, Ellie; Peters, Scott (I escaped, 2021)
"Fifteen-year-old Jon battles for freedom amid high seas, scurvy buccaneers, and Spanish fortresses when he's captured by the famous pirate, Captain Morgan, and ordered into his service. Bases on the true exploits of Captain Henry Morgan in 1670"--Back cover.